Structural and optical properties of nc-Si:H thin films deposited by layer-by-layer technique - Goh, Boon Tong; Wah, C.K.; Aspanut, Zarina; Abdul Rahman, S. (Springer, 2014)
Hydrogenated nanocrystalline silicon (nc-Si:H) thin films deposited on c-Si and quartz substrates by layerby-layer (LBL) technique using radio-frequency plasma enhanced chemical vapour deposition system. The effects of rf power on the interlayer elemental profiling, structural and optical properties of the films were investigated by Auger electron spectroscopy, Fourier transform infrared spectroscopy, Raman scattering spectroscopy, X-ray diffraction and optical transmission and reflection spectroscopy. The results revealed that the LBL deposition leads to a formation of different ranges of crystallite sizes of nc-Si corresponds 3–6 and 8–26 nm respectively. LBL deposition also demonstrated a capability to increase the crystalline volume fraction of nc-Si up to 65.3 % with the crystallite size in between 5 and 6 nm, at the rf power in between 80 and 100 W. However, the crystalline volume fraction decreased for the rf power above 100 W due to the growth of nc-Si was suppressed by the formation of SiO2. In addition, the onset of crystallization of the films deposited on c-Si and quartz substrates are different with increase in the rf power. The effects of rf power on the growth of nc-Si, and the hydrogen content, structural disorder, crystallite size of nc-Si and oxygen diffusion into the LBL layer with the change of optical energy gap under the variation of rf power are also discussed.